CLINICAL AND THERAPEUTIC ASPECTS OF CERVICAL OSTEOCHONDROSIS: PATHOGENESIS, SYNDROMOLOGY, AND MODERN TREATMENT APPROACHES - Abdulhakimov Parvoz Vaxob ugli (Research Focus International Scientific Journal, 2025)
Degenerative-dystrophic diseases of the spine represent one of the most prevalent pathologies in modern medicine. Among them, cervical osteochondrosis occupies a leading position due to its wide range of neurological and vascular complications. This article presents a comprehensive analysis of the clinical syndromes associated with cervical osteochondrosis, including radicular, reflex, vascular, spinal, and cerebral variants. The pathogenesis of neurological manifestations involves both direct degenerative changes in spinal motion segments and secondary reflex disorders resulting from irritation of nervous and autonomic structures. The main conservative treatment approaches—immobilization, pharmacotherapy (NSAIDs, COX-2 inhibitors, muscle relaxants, vasoactive agents), and physiotherapy—are discussed in detail, with emphasis on complex rehabilitation strategies. Indications for surgical intervention are outlined for severe cases of vertebrobasilar insufficiency and spinal cord compression. The study underscores the importance of timely diagnosis, pathogenetically oriented therapy, and an integrated approach to the management of cervical osteochondrosis.